2009
DOI: 10.1109/tps.2008.2012261
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a Wire-Rod Type Electrohydrodynamic Gas Pump Under Negative Corona Operation

Abstract: A wire-rod type electrohydrodynamic (EHD) gas pump was driven by a negative applied voltage with pipes of different inner diameters. An EHD gas flow was generated from a wire electrode to a rod electrode under a negative corona discharge. The flow velocity was proportional to the applied voltage and the square root of the discharge current. Before spark onset, the maximum volumetric flow rate of 43 L/min was achieved with a pipe having an inner diameter 20 mm, and the pump efficiency was higher than that of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Even though most of the researchers have been investigating the performance of positive corona discharge EHD pumps, a study of the efficiency that a wire-to-cylinder EHD pump would have under negative corona discharge has also been studied [138]. The apparatus had a diameter of 20 mm and reached a maximum air velocity of 1.7 m/s with an emitter voltage of −13 kV, while it displayed higher efficiency than that of a mechanical fan of equivalent diameter.…”
Section: A General Research On Ehd Fluid Pumpsmentioning
confidence: 99%
“…Even though most of the researchers have been investigating the performance of positive corona discharge EHD pumps, a study of the efficiency that a wire-to-cylinder EHD pump would have under negative corona discharge has also been studied [138]. The apparatus had a diameter of 20 mm and reached a maximum air velocity of 1.7 m/s with an emitter voltage of −13 kV, while it displayed higher efficiency than that of a mechanical fan of equivalent diameter.…”
Section: A General Research On Ehd Fluid Pumpsmentioning
confidence: 99%
“…Experiments showed that the EHD pump was capable of producing a maximum airflow rate of 40 l/min at −16 kV, using a pipe diameter of 20 mm with about 0.35 W input power. Another study was conducted later by Takeuchi and Yasuoka [33] using similar electrode configuration to investigate the EHD pump efficiency under negative corona discharge. Results showed that the EHD pump was more efficient by two times based on flow rate generation compared with a conventional rotary fan of equivalent diameter under the same operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This type of gas flow is known as an ionic or electric wind in the past and now called corona induced electrohydrodynamic (EHD) gas flow. EHD gas flow has been investigated in many flow control applications, such as particle flow control in electrostatic precipitators (ESPs) [2], aerodynamic flow control [3], gas pumpings [4]- [9], etc. EHD gas pumps have been developed for capillary (flow channel diameter d f < 1 mm) and narrow (1 < d f < 10 mm) flow channel for thermal management of electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Corona electrode with sharp edges, such as needle or blade electrodes [4], [5], seems to be undesirable for dc corona discharge since it is easier to transit from streamer to a spark discharge. Hence a wire-non-parallel plate EHD gas pump [6] and a wire-rod type EHD gas pump [7]- [9] use a thin metal wire as a corona electrode to obtain a stable and effective corona discharge, as proven in many commercial ESPs and copy machines. The wire-rod type EHD gas pump achieves This work is supported by a Grant-in-Aid for JSPS Fellows from the Japan Society for the Promotion of Science (NT) and NSERC of Canada (JSC, NT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation